Membangun Teologi Pendidikan Agama Kristen di Gereja Lokal - Warseto Freddy Sihombing; Seri Antonius (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2022)
Christian Religious Education (PAK) is a central part of Christianity and can be applied not only in schools, but also in local churches. This certainly requires serious handling as part of an ecclesiastical ministry. The church in carrying out its function as a place of fellowship for believers with God is bound by the teaching of God's word contained in the Bible. Education is the goal of the great commission ordered by Jesus. The delivery of God's word from the servant of God or the pastor of the local church can be conveyed to the congregation by applying the PAK pedagogical principles. In long church’s history, we have honestly recorded the strengths and weaknesses of the church while in this world. The theological basis of PAK in the local church is a biblical reason related to the importance of PAK teaching which consists of PAK tasks, processes and objectives. AbstrakPendidikan Agama Kristen (PAK) adalah bagian yang sentral dalam kekristenan dan dapat diterapkan bukan hanya di sekolah, melainkan juga di gereja lokal. Hal ini tentu membutuhkan penanganan yang serius sebagai bagian dari pelayanan gerejawi. Gereja dalam menjalankan fungsinya sebagai tempat persekutuan orang percaya dengan Tuhan terikat dengan pengajaran firman Tuhan yang terdapat dalam Alkitab. Pendidikan adalah tujuan dari amanat agung yang dipesankan oleh Yesus. Penyampaian firman Tuhan dari hamba Tuhan atau pendeta jemaat lokal dapat disampaikan kepada jemaat dengan menerapkan prinsip pedagogis PAK. Dalam perjalanan sejarah gereja yang panjang, secara jujur telah mencatat kelebihan dan kelemahan gereja selama ada di dunia ini. Dasar teologis PAK dalam gereja lokal adalah alasan alkitabiah berkaitan dengan pentingnya pengajaran PAK yang terdiri dari tugas, proses dan tujuan PAK.